Meaning in the narrrative of Charles Dickens - Chittick, Kathryn Ann (The University of Edinburgh, 1980)
Even within Dickens's own lifetime, the response of his readers moved from the enthusiastic reception of all things Pickwickian, to complaints that the looseness of the Pickwick format impaired any possible pleasure in it, for the discontinuity and repetition of such narrative seemed to exclude any meaningful sort of progression. Dickens was no philosopher, but the question of how meaning is evoked by his narrative has been generally overlooked. "The rhetoric of fiction" is by now a commonplace phrase but it is still valuable for reminding us of the fact that all works of the imagination seek in some way to "persuade." The presence of fantasy, however minimally, will always imply that life could be arranged differently, and that a deductive or syllogistic reasoning may not be the only rationale of human existence. In my research I have related an examination of Dickens's memoranda notebook and journalism to his novels, in an attempt to understand how he has organised various narrative strategies —particularly, the use of sheer length and an almost antinarrative multiplication of story and allusion—to convey his intentions. The notebook and journalism may share many topical sources with the fiction, but while turning up many noteworthy similarities, comparisons more often make apparent the possible choices of treatment available to an author, and how differences in presentation will produce significant contrasts in the expectations aroused and the resolutions achieved in discussion of the same idea. The experience of picking out various memoranda which one recogiizes as eventually, and possibly surprisingly, coming together in one novel, make the critic sense that it is not just unique entities or pellets of belief which go to make up a novel's "meaning" i it is present in the very decision to speak through story and in the nature of the narrative approach. Dickens perhaps demonstrates more radically than any of his contemporaries that a twenty-part novel is, in fact, infinitely divisible in a variety of ways» why did he not repeat the successful early patterns? How did the sequentiality of Pickwick Papers gradually lead into the balance of Bleak House? As well, it should be noted that Dickens undertook the establishment of a journal on five occasions during his career as a novelist. The origins of Pickwick Papers, Nicholas Nickleby, Oliver Twist, and The Old Curiosity Shoo show Dickens's early oscillations between journalism and fictionwriting. The thesis considers why this work seemed permanently attractive to him, and noting also that these ventures repeatedly ended in the writing of novelistic prose—how Dickens's novels can be seen in some sense to be his more successful forms of "miscellany."